Framework to Classify Reverse Cardiac Remodeling With Mechanical Circulatory Support: The Utah-Inova Stages. (May 2021) - Shah, Palak; Psotka, Mitchell; Taleb, Iosif; Alharethi, Rami; Shams, Mortada A.; Wever-Pinzon, Omar; Yin, Michael; Latta, Federica; Stehlik, Josef; Fang, James C.; Diao, Guoqing; Singh, Ramesh; et al.
Abstract : Background: Variable definitions and an incomplete understanding of the gradient of reverse cardiac remodeling following continuous flow left ventricular assist device (LVAD) implantation has limited the field of myocardial plasticity. We evaluated the continuum of LV remodeling by serial echocardiographic imaging to define 3 stages of reverse cardiac remodeling following LVAD. Methods: The study enrolled consecutive LVAD patients across 4 study sites. A blinded echocardiographer evaluated the degree of structural (LV internal dimension at end-diastole [LVIDd]) and functional (LV ejection fraction [LVEF]) change after LVAD. Patients experiencing an improvement in LVEF ≥40% and LVIDd ⩽6.0 cm were termed responders, absolute change in LVEF of ≥5% and LVEF <40% were termed partial responders, and the remaining patients with no significant improvement in LVEF were termed nonresponders. Results: Among 358 LVAD patients, 34 (10%) were responders, 112 (31%) partial responders, and the remaining 212 (59%) were nonresponders. The use of guideline-directed medical therapy for heart failure was higher in partial responders and responders. Structural changes (LVIDd) followed a different pattern with significant improvements even in patients who had minimal LVEF improvement. With mechanical unloading, the median reduction in LVIDd was −0.6 cm (interquartile range [IQR], −1.1 to −0.1 cm; nonresponders), −1.1 cm (IQR, −1.8 to −0.4 cm; partial responders), and −1.9 cm (IQR, −2.9 to −1.1 cm; responders). Similarly, the median change in LVEF was −2% (IQR, −6% to 1%), 9% (IQR, 6%–14%), and 27% (IQR, 23%–33%), respectively. Conclusions: Reverse cardiac remodeling associated with durable LVAD support is not an all-or-none phenomenon and manifests in a continuous spectrum. Defining 3 stages across this continuum can inform clinical management, facilitate the field of myocardial plasticity, and improve the design of future investigations. Abstract : Supplemental Digital Content is available in the text.